Cancellation Of Government Procurement Of Goods/Services In Administrative Legal Aspects And Implication In Ptun - Gunawan, Anneke Catlynne; Gunadi, Chaterine Grace; Indrakusuma, Jason; Emmanuel Stutanto, Theodore Francisco (UNIVERSITAS PAKUAN, 2025)
AbstractProcurement is an activity that involves various parties in an auction or tender process to get the best offer in terms of price, quality, and efficiency. One of the problems that often arise in public procurement tenders is the unilateral cancellation of tenders by authorized officials, which has an impact on losses for bidders. This research aims to analyze the administrative law aspects in the cancellation of government procurement of goods/services and its implications in the State Administrative Court (PTUN). Using a secondary qualitative research method, this research relies on data from journals, articles, and relevant regulations. One of the cases studied is the Jakarta Administrative Court Decision No. 191/G/2019/PTUN-JKT relating to the cancellation of the auction of the DKI Jakarta Electronic Paid Road System (SJBE/ERP) project. The results showed that the cancellation of the auction carried out by the Procurement Committee did not fulfill legal procedures and the aggrieved party could challenge the decision letter to cancel the auction at the PTUN. This study recommends the importance of transparency, accountability, and the application of principles in the public procurement process to avoid injustice to the public. Keywords: Administrative Remedies, Tender, Cancellation, PTUN, Procurement of Goods/Services